Divergence and gene flow between the East Sea and the Southeast Atlantic populations of North Pacific light fish Maurolicus japonicus Ishikawa - Habib, Kazi Ahsan; Oh, Jina; Kim, Sung; Lee, Youn-Ho (Genes & genomics, 2012)
In the present study, we examined the divergence time and the magnitude of gene flow between two distantly separated populations of North Pacific light fish Maurolicus japonicus , one in the southern part of the East Sea (off Korea) and the other in the Southeast Atlantic Ocean (off Namibia). The mitochondrial 16SrDNA sequences (524 base pairs) obtained from the two populations were analyzed using the isolation with migration (IM) coalescent method as well as the conventional F ST statistic and a phylogeographic method. A significant nonzero F ST value (0.176, P<0.05) indicated genetic differentiation between the two populations. The low level of nucleotide diversity compared to the moderately high level of haplotype diversity implied that the populations have experienced a bottleneck followed by rapid growth in both populations. IM analysis suggested that these two populations most likely split approximately 500–800 K years ago during the Pleistocene climatic oscillations and that gene flow has occurred unidirectionally from the Southeast Atlantic population to the East Sea population. Nested clade phylogeographic analysis supports restricted gene flow between the two populations.